Design of Genuine Birth Environment: Midwives Intuitively Think in Terms of Evidence-Based Design Thinking. (April 2019) - Folmer, Mette Blicher; Jangaard, Karin; Buhl, Henrik
Objective: The objective of this study is to investigate a development project initiated and led by midwives. Background: The aim was to design an environment that could accommodate the wish to support professionalism while creating better and more cohesive patient treatment, improved patient safety, greater efficiency, higher quality, and stronger focus on the patient. Theory: The theoretical and analytical account is conducted within the framework of design thinking (DT), replacing the traditional evidence-based design approach with an evidence-based design thinking (EBDT) process underpinning participatory DT and co-creation. Method: Based on a longitudinal case study on a participatory design process, interviews are conducted. DT principles are used in the analysis of the interviews. Results: Genuineness arises when all users experience that the physical setting optimally underpins the birthing situation. It is essential to make visible the importance of the physical setting to human behavior in any situation. Conclusion: This study shows that midwives intuitively do EBDT. EBDT commands awareness of both research, design, midwifery care, and perspectives on space from women giving birth and their relatives. Collectively, that can provide the genuine scope of a healing birth environment.